Autonomy and Accountability in Standards-Based Reform - Watson, Susan; Supovitz, Jonathan (Education Policy Analysis Archives, 2001)
In this article we discuss the effects of one urban school district's efforts to increase the autonomy and accountability of schools and teams of teachers through a standards-based reform known as team- based schooling. Team-based schooling is designed to devolve decision-making authority down to the school level by increasing teachers' autonomy to make decisions. Increased accountability is enacted in the form of a state-level standards-based initiative. Based on our evaluation over a two-year period involving extensive fieldwork and quantitative analysis, we describe the ways that teachers, teams and school administrators responded to the implementation of team-based schooling. What are the effects of increasing school-level autonomy and accountability in the context of standards- based reform? Our analysis highlights several issues: the "lived reality" of teaming as it interacts with the existing culture within schools, the ways that teachers respond to the pressures created by increased internal and external accountability, and the effects of resource constraints on the effectiveness of implementation. We conclude by using our findings to consider more broadly the trade-off between increased autonomy and accountability on which standards-based reforms like team-based schooling are based.